Naïve and Memory CD4 T Cells Differ in Their Susceptibilities to Human Immunodeficiency Virus Type 1 Infection following CD28 Costimulation: Implications for Transmission and Pathogenesis - Riley, James L. (American Society for Microbiology, 1998)
In vitro evidence suggests that memory CD4(+) cells are preferentially infected by human immunodeficiency virus type 1 (HIV-1), yet studies of HIV-1-infected individuals have failed to detect preferential memory cell depletion. To explore this paradox, we stimulated CD45RA(+) CD4(+) (naïve) and CD45RO(+) CD4(+) (memory) cells with antibodies to CD3 and CD28 and infected them with either CCR5-dependent (R5) or CXCR4-dependent (X4) HIV-1 isolates. Naïve CD4(+) cells supported less X4 HIV replication than their memory counterparts. However, naïve cells were susceptible to R5 viral infection, while memory cells remained resistant to infection and viral replication. As with the unseparated cells, mixing the naïve and memory cells prior to infection resulted in cells resistant to R5 infection and highly susceptible to X4 infection. While both naïve and memory CD4(+) subsets downregulated CCR5 expression in response to CD28 costimulation, only the memory cells produced high levels of the β-chemokines RANTES, MIP-1α, and MIP-1β upon stimulation. Neutralization of these β-chemokines rendered memory CD4(+) cells highly sensitive to infection with R5 HIV-1 isolates, indicating that downregulation of CCR5 is not sufficient to mediate complete protection from CCR5 strains of HIV-1. These results indicate that susceptibility to R5 HIV-1 isolates is determined not only by the level of CCR5 expression but also by the balance of CCR5 expression and β-chemokine production. Furthermore, our results suggest a model of HIV-1 transmission and pathogenesis in which naïve rather than memory CD4(+) T cells serve as the targets for early rounds of HIV-1 replication.